Can a standardised aptitude test predict the training success of apprentices? : Evidence from a case study in Switzerland - Siegenthaler, Michael [Verfasser] (My University, 2011)
"Due to widely spread distrust in the signaling value of school grades, Swiss employers require external standardised aptitude test results in the process of recruiting new apprentices. However, the predictive quality of such tests has never been thoroughly researched. Therefore, this case study analyses whether aptitude tests can improve the ability of firms to predict success in apprenticeship training. I find that such tests do not add information that explains the success in VET schooling (school grades during the first and second years of apprenticeship training), the probability of unexcused vocational school absences, or the likelihood of a premature termination of the apprenticeship contract." (Autorenreferat, BIBB-Doku)
Keywords: P 2.3 Auszubildende; L 8 Diagnostik / Eignung; I 2.2.1 Westeuropa; Ausbildungsstellenbewerber; Bewerberauswahl; Einstellungsvoraussetzung; Schulleistung; Eignungstest; Einflussfaktor; Schweiz